Grammar and style - Peters, Mark 1972- (Alpha Books, 2014)
Grammar can be an intimidating subject. This guide helps you learn-- or relearn-- the essentials, and makes learning and using proper grammar simple.
Includes bibliographical references and index. - Print version record
Keywords: English language -- Handbooks, manuals, etc -- Grammar; English language -- Handbooks, manuals, etc -- Rhetoric; English language -- Handbooks, manuals, etc -- Usage; Anglais (Langue); Rhétorique; Guides, manuels, etc; English language; Grammar; English language; Rhetoric; English language; Usage; English; Languages & Literatures; English Language; Handbooks and manuals